Odour Profile of Beef Using an Electronic Nose Based on MOS-Sensor - Grigioni, Gabriela Maria; Paschetta, Fernanda; Soteras, Trinidad; Messina, Valeria Marisa (2018)
The development of the aroma and flavour of cooked meat is a very complex process in which different components react to produce chemical intermediates or final flavour volatiles compounds. The aim of the present research was to study the odour profile of beef produced under different feeding regimes and cooking conditions using an electronic nose based on MOS sensors to monitor the odour characteristics. Odour profiles of different grilled-cooked muscles were evaluated. A clear discrimination between groups corresponding to muscle was observed. Grilled-cooked samples of Longissimus dorsi muscle from animals fed to other cooking process. under different diets showed a clear discrimination between groups. Finally, Striploins samples cooked by moist-heat method tend to be different when compared.